Production technology of chilli (Capsicum annum L.) under protected cultivation - Pintu Roy Vattakunnel (Department of Agronomy, College of Agriculture, 2014)
The field experiment entitled “Production technology of chilli (Capsicum annuum L.) under protected cultivation” was conducted at Instructional Farm, College of Agriculture, Vellayani during March 2013 to September 2013 to study the performance of chilli varieties and the effect of fertigation on productivity of chilli (Capsicum annuum L.) under protected cultivation. The main plot treatments were a combination of growing conditions (poly house and open field) and fertigation (with fertigation and without fertigation) and the subplot treatments consisted of three varieties (Vellayani Athulya, Anugraha and Jwalamukhi). The study revealed that plants grown under poly house situation recorded significantly higher fruit length (11.77cm), number of fruits plant-1 (110.67), fruit yield plant-1 (604.08 g) and total fruit yield (29.54 t ha-1). Plants grown with fertigation registered higher number of fruits plant-1 (113.49), length of fruit (11.55 cm), fruit yield plant-1 (591.92 g) and total fruit yield (26.27 t ha-1). Maximum length of fruits (12.82 cm), fruit yield plant-1 (665.18 g) and total fruit yield (28.41 t ha-1) were obtained from Vellayani Athulya while, highest number of fruits plant-1 (154.21) was from Anugraha. Maximum length of fruits was observed in Vellayani Athulya grown under both poly house (12.91 cm) and open field situation (12.72 cm). Vellayani Athulya grown with fertigation also recorded maximum fruit length (13.67 cm). Vellayani Athulya recorded maximum shelf life (10.19 days) and ascorbic acid content (98.71 mg 100 g-1) where as maximum capsaicin content (1.38 per cent) was recorded by Jwalamukhi. Vellayani Athulya grown under poly house registered maximum shelf life (10.88 days) and ascorbic acid content (102.78 mg 100 g-1). Vellayani Athulya with fertigation recorded maximum ascorbic acid content (101.69 mg 100 g-1) while, Jwalamukhi grown with fertigation recorded maximum capsaicin content (1.40 per cent). Vellayani Athulya grown under poly house with fertigation recorded higher shelf life (12.00 days). Vellayani Athulya grown under poly house with fertigation recorded maximum ascorbic acid (108.74 mg 100 g-1). Maximum capsaicin was also recorded by Jwalamukhi grown under poly house with fertigation (1.43 per cent). Among growing conditions, maximum net return (Rs 5.22 lakhs ha-1) and B: C ratio (2.42) was obtained from poly house. On comparing with and without fertigation treatments, with fertigation treatments recorded maximum net return of Rs 4.46 lakhs ha-1 and among varieties, Vellayani Athulya (V1) recorded maximum net return of Rs 4.95 lakhs ha-1 and B: C ratio of 2.30.